Forming nanoparticles of water-soluble ionic molecules and embedding them into polymer and glass substrates - Kiel, Stella; Grinberg, Olga; Perkas, Nina; Charmet, Jerome; Kepner, Herbert; Gedanken, Aharon (Beilstein Journal of Nanotechnology, 2012)
This work describes a general method for the preparation of salt nanoparticles (NPs) made from an aqueous solution of ionic compounds (NaCl, CuSO4 and KI). These nanoparticles were created by the application of ultrasonic waves to the aqueous solutions of these salts. When the sonication was carried out in the presence of a glass microscope slide, a parylene-coated glass slide, or a silicon wafer the ionic NPs were embedded in these substrates by a one-step, ultrasound-assisted procedure. Optimization of the coating process resulted in homogeneous distributions of nanocrystals, 30 nm in size, on the surfaces of the substrates. The morphology and structure of each of the coatings were characterized by physical and chemical methods, such as X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM), Raman spectroscopy and X-ray photoelectron spectroscopy (XPS). After 24 h of leaching into water the nanoparticles of the inorganic salts were still present on the slides, and complete leaching of nanoparticles occurred only after 96 h. A mechanism of the ultrasound-assisted coating is proposed.
Keywords: deposition; ionic salt nanoparticles; parylene; sonochemistry